KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN GARIS LURUS - Wilda Pratiwi Aryadini Arumsari; Alpha Galih Adirakasiwi (IKIP Siliwangi, 2023)
The purpose of this research is to describe students' ability to understand mathematical concepts in solving straight line equations. This study uses a qualitative approach with descriptive research methods. The selection of research subjects through analytical observation so that 3 out of a total of 20 students in class IX at one of the schools in Karawang Regency were obtained. Data collection techniques used in this study were tests, interviews, and observations. The results showed that students in the high category had fulfilled each indicator of the ability to understand mathematical concepts; students in the moderate category have been able to fulfill the indicators of presenting concepts in various forms of mathematical representations, indicators of developing necessary and sufficient conditions for a concept and indicators of applying concepts or problem-solving algorithms, but still not fulfilling other indicators; low category students have not been able to fulfill all indicators, especially on indicators of developing necessary and sufficient conditions for a concept and indicators of using, utilizing and selecting certain procedures or operations.